LO47: Hematochezia in children with acute gastroenteritis in the emergency department: clinical phenotype, etiologic pathogens, and resource utilization. (May 2020) - Böhrer, M.; Fitzpatrick, E.; Hurley, K.; Xie, J.; Lee, B.; Pang, X.; Chui, L.; Tarr, P.; Ali, S.; Vanderkooi, O.; Freedman, S.
Abstract : Introduction: Acute bloody diarrhea obligates rapid and accurate diagnostic evaluation; few studies have described such cohorts of children. Methods: We conducted a planned secondary analysis employing the Alberta Provincial Pediatric EnTeric Infection TEam (APPETITE) acute gastroenteritis study cohort to describe the characteristics of children with acute bloody diarrhea, compared to a cohort of children without hematochezia. Children <18 years of age presenting to 2 pediatric tertiary care emergency departments (EDs) in Alberta, with ≥3 episodes of diarrhea and/or vomiting in the preceding 24 hours and <7 days of symptoms were consecutively recruited. Stools were tested for 17 viruses, bacteria and parasites. Primary outcomes were clinical characteristics and pathogens identified. Secondary outcomes included interventions and resource utilization. Results: Of 2257 children enrolled between October 2015 and August 2018, hematochezia before or at the index ED visit was reported in 122 (5.4%). Compared to children with nonbloody diarrhea, children with hematochezia had longer illness duration [59.5 vs. 41.5 hrs, difference 10.6, 95% CI 3.5, 19.9], more diarrheal episodes in a 24-hour period [8 vs. 5, difference 3, 95% CI 2, 4], and less vomiting [55.7% vs. 91.1%; difference -35.3%; 95% CI -44.7, -26.3]. They received more intravenous fluids [32.0% vs. 18.3%; difference 13.7%, 95% CI 5.5, 23.0], underwent non-study stool testing [53.7% vs. 4.8%; difference 49.0%, 95% CI 39.6, 58.0], experienced longer ED visits [4.1 vs. 3.3 hours, difference 0.9, 95% CI 0.3, 1.0] and were more likely to have repeat healthcare visits within 14 days [54.8% vs. 34.2%; difference 20.6%, 95% CI 10.8, 30.1]. A bacterial enteric pathogen was found in 31.9% of children with hematochezia versus 6.6% without bloody diarrhea (difference 25.4%, 95% CI 17.2, 34.7). In children with hematochezia, the most commonly detected bacteria were Salmonella spp. (N = 15), Shiga toxin-producing E. coli (N = 9), Campylobacter spp. (N = 7), and Shigella spp. (N = 5). Viruses were detected in 32.8% of children with bloody diarrhea, most commonly adenovirus (N = 15), norovirus (N = 14), sapovirus (N = 8) and rotavirus (N = 7). Conclusion: Children with hematochezia differed clinically from those without hematochezia and required more healthcare resources. While bacterial etiologies are common, several viruses were also detected.